TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH (PPAT) TERHADAP PIHAK YANG MEMBERIKAN KETERANGAN PALSU - Annisa Nur Azizah (Legal Standing : Jurnal Ilmu Hukum, 2023)
In carrying out their position, Land Titles Registrar is responsible for making authentic deed. The research method was normative research method, which is collecting legal materials using literature study and drawing conclusion based on the legal materials. The present study found that the role of Land Titles Registrar in carrying their position in making deed which isn’t based on the making of deed or the procedure of making deed, causes the deed with perfect power to be legally defective. Therefore, in carrying out their position, Land Titles Registrar must be responsible for the legal defect of a deed. For this reason, the responsibilities of Land Titles Registrar could be administrative, civil, and criminal responsibilities. If the procedure of making a deed isn’t met, Land Titles Registrar could be asked for compensation by the Buyer. Furthermore, the party or appearer who isn’t based on pre-contract good faith, in this case the agreed agreement, could be cancelled for not fully meeting the subjective principle of the agreement.